Joint Attack: A New Privacy Attack for Incremental Data Publishing - Torsak Soontornphand (2018)
© 2016 IEEE. Although there are several privacy approaches, which are designed for incremental data publishing, these privacy approaches can cope with only similarity and difference attacks. In this paper, we propose a new pattern of privacy attack for incremental data publishing, so called joint attack. We first illustrate the joint attack by example. Then, the investigation on the characteristics of the joint attack is made. Finally, we propose a simple yet effective algorithm to resolve such joint attack as well as the two well-known attacks, i.e. similarity and difference attacks. From the experimental results, we can conclude that our approach is effective.